1996
DOI: 10.1099/00207713-46-2-397
|View full text |Cite
|
Sign up to set email alerts
|

Desulfotomaculum thermocisternum sp. nov., a Sulfate Reducer Isolated from a Hot North Sea Oil Reservoir

Abstract: The organism described in this paper, strain ST90T (T = type strain), is a thermophilic, spore-forming, rod-shaped sulfate reducer that was isolated from North Sea oil reservoir formation water. In cultivation the following substances were used as electron donors and carbon sources: H,-CO,, lactate, pyruvate, ethanol, propanol, butanol, and C, to C,, and C,, to C,, carboxylic acids. Sulfate was used as the electron acceptor in these reactions. Lactate was incompletely oxidized. Sulfite and thiosulfate were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
1
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 49 publications
3
84
1
2
Order By: Relevance
“…Propionate uptake has been reported in both Gramnegative (Syntrophobacter and Smithella) and Gram-positive (Desulfotomaculum and Pelotomaculum) organisms (Boone and Bryant, 1980;de Bok et al, 2001;Imachi et al, 2002;Nilsen et al, 1996;Plugge et al, 2002). Because Proteobacteria-related clones from days 743, 841, and 939 were closely related to the genus Syntrophobacter (Figure 4 and Table II) and no clones related to Grampositive propionate utilizers were detected in the clone libraries, propionate uptake in the reactor was attributed to Syntrophobacter.…”
Section: Phylogenetic Analysismentioning
confidence: 91%
“…Propionate uptake has been reported in both Gramnegative (Syntrophobacter and Smithella) and Gram-positive (Desulfotomaculum and Pelotomaculum) organisms (Boone and Bryant, 1980;de Bok et al, 2001;Imachi et al, 2002;Nilsen et al, 1996;Plugge et al, 2002). Because Proteobacteria-related clones from days 743, 841, and 939 were closely related to the genus Syntrophobacter (Figure 4 and Table II) and no clones related to Grampositive propionate utilizers were detected in the clone libraries, propionate uptake in the reactor was attributed to Syntrophobacter.…”
Section: Phylogenetic Analysismentioning
confidence: 91%
“…However, 16s rDNA sequence analyses are unable to separate closely related species with similarity levels of 97% or higher. Their relationships are best determined by phenetic and genetic similarities (14,27,38). Strain B54T differs phenotypically, serologically, and genetically from the other validly described Desulfobacter species.…”
Section: Discussionmentioning
confidence: 99%
“…However, fine details concerning the phylogenetic coherence of this genus and the relatedness of its species have not yet been fully explored. Most previous studies included only a few species, and even the most recently published phylogenetic trees did not include more than eight or nine species (14,18,31). These studies showed that the majority of species cluster together to form a major subline of descent among the several clusters encompassing clostridia and their non-spore-forming and/or coccoid relatives (4).…”
mentioning
confidence: 94%